Profiles from the kitchen : what great cooks have taught us about ourselves and our food - Baker-Clark, Charles Allen (University Press of Kentucky, 2006)
In Profiles from the Kitchen, Charles A. Baker-Clark offers a collection of portraits of well-known culinary figures who have worked in different ways to shape our relationship with food. Despite their diverse personalities, backgrounds, and interests, Baker-Clark's subjects are a testament to the fact that both cooking and eating are endeavors well worth learning and sustaining. Profiles from the Kitchen includes well-known food writers such as M.F.K. Fisher, Eugene Walter, Elizabeth David, and John T. Edge; famous cooks such as Julia Child and James Beard; and contemporary chefs such as Rick.